Application of boundary estimation method for determining aircraft aerodynamic parameters - Миронович, M. B.; Сильвестров, А. Н.; Стенин, A. A.; Хотячук, Р. Ф. (Proceedings of National Aviation University (archive), 2000)
Described is boundary estimation method of aircraft aerodynamic parameters which allows to determine with sufficient accuracy aerodynamic coefficients, necessary for diagnosis of available aeronautical engineering and for prediction of new real speciments